Contextualization of Female Imam Hadith in Indonesia: An Analysis of Sanad and Matan - Khaerul Umam; Atiyatul Ulya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The hadith prohibiting female imams has always been a topic of discussion among Muslims in Indonesia, as this argument has always been used as an obstacle to empowerment. Therefore, this paper aims to analyze the prohibition of female imams from various perspectives and its contextualization for Muslims in Indonesia. The method used is descriptive qualitative, sourced from literature studies with a critical approach to the sanad and matan of the hadith. The results of this study conclude that from the perspective of sanad studies, the hadith regarding the prohibition of female imams is of weak quality and from the perspective of matan, it is also problematic because it contradicts the verses of the Qur'an. The practice of female imams in the contemporary era in Indonesia is permissible if there is a valid religious reason, such as the absence of competent men, or if it is based on a mutual agreement that results in the common good.